Characteristics of T-Cell Receptor Repertoire and Correlation With EGFR Mutations in All Stages of Lung Cancer - Yang, Huaxia; Wang, Yadong; Jia, Ziqi; Wang, Yanyu; Yang, Xiaoying; Wu, Pancheng; Song, Yang; Xu, Huihui; Gu, Dejian; Chen, Rongrong; Xia, Xuefeng; Bing, Zhongxing; et al. (Frontiers in Oncology, 2021)
Lung cancer is the leading cause of cancer-related death worldwide, and its occurrence is related to the accumulation of gene mutation and the immune escape of tumor. Sequencing of T cell receptor (TCR) repertoire can reveal immunosurveillance status in tumor microenvironment, which is related to tumor escape and immunotherapy. This study aimed to determine the characteristics and clinical significance of the T-cell receptor (TCR) repertoire in lung cancer. To comprehensively profile the TCR repertoire, the results of TCR repertoire from high throughput sequencing of 93 lung cancer patients was analyzed. We found that the TCR clonality of tissues was not affected by individual characteristics in terms of age, gender, smoking and histology. As expected, TCR clonality correlated with tumor–node–metastasis (TNM) staging. The correlation between TCR and EGFR was also investigated. EGFR non-L858R patients showed higher clonality than L858R patients. Further, the overlap index (OLI) was analyzed of postoperative peripheral blood of non-distant metastasis lung cancer patients. The same difference that EGFR non-L858R patients have higher OLI has also been found. Meanwhile, OLI showed a positive correlation with several clinical characteristics, such as the tumor mutation burden (TMB) of tissues and maximum somatic allele frequency (MSAF) of blood. In conclusion, TCR clonality and OLI were correlation with clinical characteristics of lung cancer patients and the differences of TCR clonality and OLI in EGFR subtypes provide important information for understanding the different EGFR subtypes patients showing differential responses to treatment.